Long-term memory problems in children and adolescents : assessment, intervention, and effective instruction - Dehn, Milton J. (Wiley Online Library., 2010)
"This book will be a valuable resource for psychologists and educators who work with children or adolescents who are having difficulties with memory and learning. Translating theory and research into practice is a talent that Dr. Dehn possesses and we will benefit from his professional skills."--The Foreword by Daniel C. Miller, PhD, ABPP, ABSNP, NCSP. An indispensable guide that examines the effect of long-term memory functions on children's learning Long-Term Memory Problems in Children and Adolescents: Assessment, Intervention, and Effective Instruction is the first book of its kind for psychologists, school psychologists, and special education teachers who need an overview of long-term memory as it relates to learning and education. It presents the best practices for assessing long-term memory functions, as well as selecting and using evidence-based instructional practices with memory-impaired students.